Shoebox: Mixing storage and display of digital images in the home - Banks, Richard; Sellen, Abigail (TEI 2009 - Proceedings of the 3rd International Conference on Tangible and Embedded Interaction, 2009)
This paper describes the rationale and design process for Shoebox, a “digital box” that combines the storage and display of digital images in the home in one unit. By combining these two functions in one, Shoebox attempts to bridge the divide between the location within a home where digital content is typically stored, and the means by which it can be put on display, as well as provide a form factor that encourages co-located sharing of images.